Antiplatelet activity of astaxanthin in control- and high cholesterol-fed rats mediated by down-regulation of P2Y12, inhibition of NF-κB, and increasing intracellular levels of cAMP. (19th May 2021) - Satti, Huda H.; Khaleel, Eman F.; Badi, Rehab M.; Elrefaie, Amany O.; Mostafa, Dalia G.
Abstract: This study evaluated the antiplatelet effect of the plant carotenoid, astaxanthin (ASTX) in rats fed either control or high cholesterol plus cholic acid diet (HCCD) and possible underlying mechanisms. Adult male Wistar rats were divided into four groups (n = 8/each), namely, control (fed normal diet), control + ASTX (10 mg/kg/day), HCCD-fed rats, and HCCD + ASTX-treated rats. Diets and treatments were orally administered daily for 30 days. In both control and HCCD-fed rats, ASTX significantly increased fecal levels of triglycerides and cholesterol, reduced platelet count, prolonged bleeding time, and inhibited platelet aggregation. It also reduced platelet levels of reactive oxygen species (ROS) and Bcl-2; thromboxane B2 (TXB2) release; and the expression of P2Y12, P -selectin, and CD36 receptors. Moreover, the activity NF-κB p65 and Akt was inhibited. Concomitantly, it increased the protein levels of cleaved caspase-3 and vasodilator-stimulated phosphoprotein ( p -VASP) as well as intracellular levels of cAMP. However, in HCCD-fed rats, the effects of ASTX were associated with reduced serum levels of ox-LDL-c and fasting plasma glucose levels. In conclusion, antiplatelet effects of ASTX involve ROS scavenging, inhibiting NF-κB activity, down-regulating P2Y12 expression, and increasing intracellular levels of cAMP that are attributed to its antioxidant, hypolipidemic, and anti-inflammatory effects.